2020
DOI: 10.1002/cptc.202000051
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Spectral Properties of gem‐Dimethyl Chlorin Photosensitizers

Abstract: Chlorins that bear a gem-dimethyl group, which attributes their resistance to oxidation, are of interest for applications in photomedicine. Herein, we present the synthesis and the photophysical properties of two geminal-dimethyl chlorins (dihydroporphyrins) and their free base counterparts that act as efficient singlet oxygen generators and thus exhibit potential for use in photodynamic therapy (PDT) as anticancer or antimicrobial agents upon further derivatization. A complete characterization of their spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Chlorins are tetrapyrrolic structures, similar to porphyrins, except that one of the pyrrole rings is reduced. It was shown that the Zn(II) chlorin Chlorin-2 displayed an increased ISC rate, a higher triplet excited state quantum yields and a more efficient 1 O2 generation than its free-base counterpart Chlorin-1 as a result of the internal HAE [63]. Experimental results shown in ethanol [63].…”
Section: Bodipys and The Heavy Atom Effectmentioning
confidence: 96%
“…Chlorins are tetrapyrrolic structures, similar to porphyrins, except that one of the pyrrole rings is reduced. It was shown that the Zn(II) chlorin Chlorin-2 displayed an increased ISC rate, a higher triplet excited state quantum yields and a more efficient 1 O2 generation than its free-base counterpart Chlorin-1 as a result of the internal HAE [63]. Experimental results shown in ethanol [63].…”
Section: Bodipys and The Heavy Atom Effectmentioning
confidence: 96%
“…18 It is well established that the introduction of halogen atoms or transition metals can enhance the efficiency of this ISC, and therefore the triplet and singlet oxygen quantum yield. 50 The fluorescence lifetimes revealed a single exponential decay, suggesting the presence of only one population (for more detailed results please see the ESI, † Fig. S19).…”
Section: Papermentioning
confidence: 99%
“…33 Some research studies describe that the macrocycle distortion from the planarity and enhanced conformational dynamics can induce some destabilization of the π-system, which may lead to considerably shorter lifetimes. 50 Considering that the insertion of the metal ion can influence the thermal behaviour of the heterocyclic-fused chlorins, a thermal decomposition/sublimation study by TGA of the free-base and metal-complexes for the pyrrolidine and isoxazolidine-fused chlorins was carried out. The thermograms of the pyrrolidine and isoxazolidine-fused metallochlorins are presented in Fig.…”
Section: Papermentioning
confidence: 99%
“…Chlorins are tetrapyrrolic structures, similar to porphyrins, except that one of the pyrrole rings is reduced. It was shown that the Zn(II) chlorin Chlorin-2 displayed an increased ISC rate, a higher triplet excited state quantum yields and a more efficient 1 O 2 generation than its free-base counterpart Chlorin-1 as a result of the internal HAE [ 63 ].…”
Section: The Heavy Atom Effect In Bodipys and Chlorinsmentioning
confidence: 99%
“…These methods can predict the structural, energetic, and spectroscopic properties of compounds for the ground-state and excited-state properties of PSs. First, the geometry of the relevant compound is optimized, using a certain functional (usually a hybrid functional such as B3LYP or M06 [ 63 , 85 ]) and a basis set. Generally, basis sets leading to more accurate results cost significantly more computational effort.…”
Section: Transition Metal Triplet Photosensitizersmentioning
confidence: 99%